Antimicrobial Mechanism of Dihydroquercetin against Escherichia coli - CAI Jin, YAN Ran, WANG Mengliang, WANG Qi (Shipin Kexue, 2023)
Foodborne pathogens pose a major challenge to food safety. Dihydroquercetin (DHQ) can be used as a food preservative; however, its antimicrobial mechanism is still unclear. This study found that DHQ had significant antimicrobial activity against Staphylococcus aureus, Bacillus subtilis, Escherichia coli, Proteus vulgaris, Enterobacter aerogenes and Candida tropicalis (P < 0.05), the effect being most pronounced against E. coli. The antimicrobial mechanism against E. coli was investigated. Observation by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) revealed that the DHQ-treated cells became distorted and exhibited phenomena such as adhesion, folding, plasmolysis, and the occurrence of vacuoles. DHQ resulted in a significant increase in the level of reactive oxygen species (ROS) inside the cell membrane as determined using a fluorescence probe. The determination of Annexin V-FITC/P kit showed that cell membrane permeability significantly increased with increasing DHQ concentration (P < 0.05) and cell membrane integrity was damaged. Cell membrane potential measurement by Rhodamine 123 staining revealed that DHQ caused cell membrane depolarization, leading to a significant reduction in membrane potential (P < 0.05). Moreover, DHQ caused intracellular Ca2+ leakage, which perturbed the growth, metabolism and functional activity of E. coli. DHQ interfered with the cell cycle of E. coli as determined using propidium iodide/ribonuclease (PI/RNase) staining buffer. These findings revealed that DHQ can inhibit E. coli growth mainly by acting on the cell membrane and consequently affecting the normal passage of cells.